Features of development of the violin art in the modern theatre - Buchma-Bernatska, Olga; Chystiakova, Natalia; Bazylchuk, Leonid; Putiatytska, Olha; Kopytsia, Marianna (Linguistics and Culture Review, 2021)
The foundation of the scientific basis for understanding the processes of development of modern violin art is relevant, since it allows discovering the foundations and results of transformations in the musical consciousness. The relevance of the study is determined by the decisive modifications that occur in the space of culture and affect the type of modern theatrical art. The purpose of this study is a comprehensive analysis of specific features of the violin art in the modern theatre. For this purpose, the following research methods were employed in this study: the method of analysis and the method of synthesis, induction and deduction, comparative historical and logical analysis, as well as the positions of scientific objectivity, systematisation in the study of works of violin art. The authors of the study analysed and summarised features of the development of the violin art in the modern theatre of the 21st century. The modern theatrical creativity with the use of violin art is considered from the standpoint of consistency, as a kind of artistic integrity, in which the manner of performance, repertoire, and the choice of the genre of performance play a certain role.